Utilization of Various Levels of Shading and Organic Fertilizer on Morphology, Production, and Nutrient Composition of Panicum maximum cv. Mombasa - Iwan Herdiawan; Slamet Widodo (Buletin Peternakan, 2022)
Panicum maximum cv. Mombasa is a type of grass that is known resistant to shade and responsive to fertilization. This study aimed to determine the morphology and production of Panicum maximum cv. Mombasa on various levels of shading and organic fertilizer. The soil used in this study was brown latosol. This study used a completely randomized design (CRD) with a factorial pattern consisting of three levels of shade (0%, 36%, and 72%) and two dose factors of organic fertilizer (0 g/pot and 500 g/pot). The parameters in this study consisted of morphology (plant height, number of leaves, number of tillers), plant production (biomass production, stem production, leaf production, and leaf/stem ratio), and nutrient composition (crude protein, extract ether, gross energy, and crude fibre). All data were observed in five replicates. The results showed that the level of shade up to 72% did not affect plant morphology. An increasing level of shading showed a significant increase (p<0.05) in the number of leaves of plant. Shading level decrease (p<0.05) biomass production, leaf, stem, LSR, and crude fibre content. The fertilizer application improved (p<0.05) plant morphology and production. The best interaction between growth and production was obtained in the treatment control (without shading) and fertilization of 500 g/pot. Based on the finding of this study, Panicum maximum cv. Mombasa can be developed into shade-tolerant grass in Indonesia